2021
DOI: 10.1002/admt.202001137
|View full text |Cite
|
Sign up to set email alerts
|

Improved Long‐Term Stability and Reduced Humidity Effect in Gas Sensing: SiO2 Ultra‐Thin Layered ZnO Columnar Films

Abstract: The undoped and metal‐doped zinc oxide columnar films (ZnO:Sn, ZnO:Fe, ZnO:Ag, and ZnO:Cu) are covered with an ultra‐thin layer of SiO2 (10–20 nm). The electrical, UV, and volatile organic compounds (VOCs) sensing properties are evaluated under different ambient conditions for ≈7 months to investigate the impact of the top SiO2‐layer on the long‐term stability of samples. The obtained results show a high immunity of sensing properties of SiO2‐coated samples to humidity. Furthermore, gas sensing measurements sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Figure S9 shows that the current–voltage characteristics show ohmic character at room temperature and operating temperatures of 150 and 200 °C. The I – V electrical curve changes at elevated operating temperatures between 250 and 350 °C, demonstrating the nonlinear behavior of the sensor due to an increase of its conductivity. It was also observed that the electrical current values are quite small, on the order of microamperes, up to the operating temperature of 200 °C. However, the value of the electrical current increases in the order of milliamperes after raising the operating temperature from 250 to 350 °C because of the increase in electrical conductivity. ,, …”
Section: Resultsmentioning
confidence: 94%
“…Figure S9 shows that the current–voltage characteristics show ohmic character at room temperature and operating temperatures of 150 and 200 °C. The I – V electrical curve changes at elevated operating temperatures between 250 and 350 °C, demonstrating the nonlinear behavior of the sensor due to an increase of its conductivity. It was also observed that the electrical current values are quite small, on the order of microamperes, up to the operating temperature of 200 °C. However, the value of the electrical current increases in the order of milliamperes after raising the operating temperature from 250 to 350 °C because of the increase in electrical conductivity. ,, …”
Section: Resultsmentioning
confidence: 94%
“…Meanwhile, the H2O on the surface of the sensing film, When the testing chamber contained a certain amount of n-butanol by injection, the chemisorbed oxygen ions and their derivatives on the surface of the sensing materials would react with the gas molecules of the n-butanol, and then caused the backdonation of the trapped electrons to the depletion layers, resulting in the decrease in the sensor resistance due to the reduction in the range of depletion region and the height of the barriers between the nanobelts [56,57]. Meanwhile, the H 2 O on the surface of the sensing film, one of the byproducts in the reaction described above, would further decrease the resistivity of the sensor [58]. Regarding the enhanced gas-sensing property of 0.61 at% Pb-doped ZnO porous nanobelts, it is worth noting that the gas-sensing process of pristine ZnO porous nanobelts was short of the sufficient adsorbed oxygen molecules and oxygen vacancies generated from the dopant of Pb.…”
Section: Sensing Mechanismmentioning
confidence: 99%
“…It is evident from Figure 11b that the aluminum-doped ZnO reduced the sensing response from 50 to 30 %, however, the nickel-doped ZnO maintained the sensing response and finally, the pure ZnO showed a slight increase in the sensing response, as previously reported by Bie et al [81] The causes of fluctuation have been researched beforehand, these can be humidity, temperature, and surface contaminations from the atmosphere. [82,83] The discrepancies in the sensing responses are due to the surface oxidation or reduction mechanics of the ZnO surface. Further detailed analysis with respect to time is necessary to understand the stability properties of ZnO sensors.…”
Section: Co 2 Gas Sensing Propertiesmentioning
confidence: 99%